On the Ample Service Assumption of Palm's Theorem in Inventory Modeling - Gross, Donald (Management Science, 1982)
A key assumption of much of the continuous review inventory modeling work is that orders placed do not queue up, so that there is complete order crossing and hence order lead times are strictly independent random variables. This paper investigates the effects of this assumption (which is almost never true).